The management of stress urinary incontinence: A case report - Preshani Reddy (AOSIS, 2015)
Introduction: Conservative management is the first option for patients with stress urinary incontinence (SUI). However, successful management of women diagnosed with SUI is dependent on a proper assessment and a tailored treatment plan. This case report aims to show the effectiveness of physiotherapy management in a 42-year-old patient diagnosed with SUI. Patient presentation: The patient's main complaints were involuntary loss of urine on coughing, sneezing and lifting of heavy objects, which started following the birth of her third child. Management and outcome: The patient was taught the 'Knack' manoeuvre and provided with a tailored pelvic floor exercise programme. Improvement was noted at the third visit and the patient no longer had involuntary episodes. Conclusion: This case report shows the successful outcome of conservative management in a patient with stress urinary incontinence.